The metamorphic evolution of Paleoproterozoic eclogites in Kuru-Vaara, northern Belomorian Province, Russia: Constraints from P-T pseudosections and zircon dating - Liu, Fenglin; Zhang, Lifei; Li, Xiaoli; Slabunov, Alexander I.; Wei, Chunjing; Bader, Thomas (Precambrian Research, 2017)
The rare occurrence of Precambrian eclogite has been used to argue when plate tectonics initiated. Wellpreserved kyanite-bearing eclogites were collected in the Kuru-Vaara quarry, northern Belomorian Province, Fennoscandian Shield. Textural observations and phase equilibria modeling were applied to constrain their P-T evolution. The eclogite is characterized by the peak pressure assemblage garnet + omphacite + kyanite + amphibole + quartz. The garnet has inclusions of zoisite, omphacite and kyanite. This omphacite with high jadeite (up to 33 mol%) and 5% Ca-Eskola content bears oriented rods of quartz, amphibole, and rutile. Omphacite was replaced by diopside + plagioclase +/- orthopyroxene symplectites and garnet surrounded by plagioclase coronas. Kyanite was mantled by the assemblage sapphirine + spinel + plagioclase +/- scapolite. The symplectites of diopside + plagioclase +/- orthopyroxene are further replaced by amphibole. P-T estimates of peak eclogite fades conditions are c. 18-20 kbar and 720-820 degrees C. The granulite facies assemblages formed at c. 11-13 kbar and 870-915 degrees C. Zircon U-Pb dating reveals the protolith ages of 2802-2929 Ma for the eclogites. The c. 1896 Ma zircon ages correspond to the time of prograde metamorphism in eclogite fades. The age of 1885 +/- 7 Ma for a corundum-bearing mica pegmatite vein that intruded into the eclogites reflects the infiltration of fluid at amphibolite facies conditions. Thus, the Kuru-Vaara eclogite was metamorphosed during the Paleoproterozoic, not the Archean. The P-T path of Kuru-Vaara eclogites was characterized by eclogite fades metamorphism overprinted by granulite fades and retrograde amphibolite fades metamorphism within c. 10 Ma. This process reflects the fast exhumation of the eclogites. The increase in temperature from eclogite to granulite facies in the HT-UHT domain suggests a hot Precambrian tectonic environment. (C) 2016 Elsevier B.V. All rights reserved. National Natural Science Foundation of China [41121062, 41311120071] SCI(E) ARTICLE 31-47 289